2021
DOI: 10.1186/s12889-021-11992-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unsafe sexual behavior among sexually active Chinese University students, Hebei Province, 2019

Abstract: Background Healthy sexual behavior is critical for controlling the HIV/AIDS epidemic among university students, particularly in regions with increasing infection rates among university students in China. Methods This study investigated the prevalence of unhealthy sexual behavior in the past 6 months and the associated demographic and psychosocial factors among sexually active Chinese university students. Self-identified sexually active Chinese univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…This study showed that participants who lack basic knowledge of HIV/AIDS transmission and prevention methods are two times more likely to engage in risky sexual behaviors than their counterparts. This finding is supported by studies conducted in Nigeria ( 44 ), China ( 45 ), and the USA ( 46 ). The reason could be that participants who have good knowledge will outweigh the risk of contracting HIV and will be cautious in their sexual relationships ( 47 , 48 ).…”
Section: Discussionsupporting
confidence: 70%
“…This study showed that participants who lack basic knowledge of HIV/AIDS transmission and prevention methods are two times more likely to engage in risky sexual behaviors than their counterparts. This finding is supported by studies conducted in Nigeria ( 44 ), China ( 45 ), and the USA ( 46 ). The reason could be that participants who have good knowledge will outweigh the risk of contracting HIV and will be cautious in their sexual relationships ( 47 , 48 ).…”
Section: Discussionsupporting
confidence: 70%